Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.3390/su12051776
|View full text |Cite
|
Sign up to set email alerts
|

Does Structural Capital Affect SDGs Risk-Related Disclosure Quality? An Empirical Investigation of Italian Large Listed Companies

Abstract: In a context of widespread acceptance and implementation of the United Nations Sustainable Development Goals (SDGs), this paper discusses the possible relationship between intellectual capital (IC) and nonfinancial information (NFI), particularly related to SDGs and corporate social responsibility (CSR) in a stakeholder engagement perspective. Prior studies called for further investigation about nonfinancial risk disclosure and claimed that companies mandated to disclose risk-related information tend to focus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 73 publications
1
17
0
Order By: Relevance
“…Nevertheless, previous literature has focused on specific SDG disclosures, such as the case of Goal 12, “responsible consumption and production”, and Goal 1, “no poverty” (Beacom et al , 2020; Sala and Castellani, 2019). Also, as suggested by De Luca et al (2020), research on SDG disclosure is still a novel field, which requires longitudinal analysis by including multiple territorial contexts. In this sense, to enrich the comprehension of the pervasion of SDGs among the food and beverage companies, a more holistic research approach is required.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, previous literature has focused on specific SDG disclosures, such as the case of Goal 12, “responsible consumption and production”, and Goal 1, “no poverty” (Beacom et al , 2020; Sala and Castellani, 2019). Also, as suggested by De Luca et al (2020), research on SDG disclosure is still a novel field, which requires longitudinal analysis by including multiple territorial contexts. In this sense, to enrich the comprehension of the pervasion of SDGs among the food and beverage companies, a more holistic research approach is required.…”
Section: Introductionmentioning
confidence: 99%
“…Completeness is also linked to the different stakeholder expectations that change over time (Mio et al , 2020) with pressures for a more reliable, trustworthy, and objective disclosure for investors' decisions. In this way, De Luca et al (2020) discussed the evolution from voluntary to mandatory disclosure, highlighting that NFI has increased pressure on organizations to set up risk management tools that assess sustainability risks. De Luca et al (2020) found that investors and stakeholders pay a great deal of attention to the information that demonstrates how management addresses decisions based on risky scenarios.…”
Section: Resultsmentioning
confidence: 99%
“…Empirical evidence shows that the company sector influences the level of its social, environmental, and sustainability disclosure (Raucci and Tarquinio, 2020) Other research identifies specific circumstances under which the comparability must be considered. For instance, De Luca et al (2020) suggest ways to increase the quality of risk-related disclosure with risk assessment procedures and processes, internal structures, as well as the organizational philosophy and techniques.…”
Section: Resultsmentioning
confidence: 99%
“…In this regard, the current study assumed that substantial investment in structural capital is anticipated to improve the performance of financial organizations. Previous studies indicated that an organization having weak procedures and systems for tracking its actions often fails to achieve competence regarding performance (De Luca et al 2020). Conversely, an organization with a strong structural capital is expected to possess an encouraging work culture for employees that helps them to learn innovative knowledge with refined and improved performances (Asiaei et al 2020).…”
Section: Structural Capitalmentioning
confidence: 99%